Novel inflammasome and oxidative modulators in Parkinson's disease: A prospective study. (24th August 2022) - Roy, Akash; Banerjee, Rebecca; Choudhury, Supriyo; Chatterjee, Koustav; Mondal, Banashree; Dey, Sanjit; Kumar, Hrishikesh
Graphical abstract: Highlights: In Parkinson's disease, NLRP3 inflammasome and oxidative markers increased significantly over a year. In line with peripheral markers Motor-severity of Parkinson's disease also worsened at the same time. Inflammasome and Oxidative modulators correlate with Parkinson's disease progression. Abstract: Introduction: The etiopathogenesis of Parkinson's disease (PD) is not clear. Yet, it seems likely that inflammation as well as oxidative stress plays a major role in the disease pathogenesis. Based on our previous findings, we aimed to investigate prospective changes in peripheral inflammasome and oxidative modulators in relation to the progression of motor symptoms and severity of PD. Methods: Levels of inflammatory and oxidative markers in the serum of PD patients and healthy controls were estimated by quantitative ELISA and spectrophotometric methods at the baseline and at the end of one year. Results: In PD patients, serum NLRP3 inflammasome and IL-1β levels increased significantly over a year, compared to the baseline. The average enzymatic activity of serum SOD1 was also augmented at one-year follow-up. Alongside these serummarker changes, the mean motorseverity of this patient cohort worsened over the time period. Conclusion: This pioneering study identified a novel association of peripheral inflammatory and oxidative markers with the progression of PD. Correlation of these serum proteins with the central pathological changes in PD and disease severity in a prospective manner might be useful not only for prognostication, but for understanding disease mechanisms and for planning future therapeutic strategies.